2023
DOI: 10.3758/s13415-022-01054-4
|View full text |Cite
|
Sign up to set email alerts
|

Value certainty and choice confidence are multidimensional constructs that guide decision-making

Abstract: The degree of certainty that decision-makers have about their evaluations of available choice alternatives and their confidence about selecting the subjectively best alternative are important factors that affect current and future value-based choices. Assessments of the alternatives in a given choice set are rarely unidimensional; their values are usually derived from a combination of multiple distinct attributes. For example, the taste, texture, quantity, and nutritional content of a snack food may all be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 62 publications
(152 reference statements)
5
9
1
Order By: Relevance
“…Previous research has suggested that decisionmakers refine their value estimates for choice options during deliberation, prior to committing to the choice (Lee & Daunizeau, 2020, 2021. It has been shown that the predictive effect of dV on consistency is larger when dV is calculated using postchoice ratings (i.e., dV2) rather than prechoice ratings (Lee & Coricelli, 2020;Lee & Daunizeau, 2020, 2021Lee & Hare, 2023;Lee & Holyoak, 2021; similar results were also reported in Simon, Krawczyk, et al, 2004;Simon & Spiller, 2016). The present study replicates this finding.…”
Section: Choice-induced Changes In Preference Are Instrumental To Dec...supporting
confidence: 88%
See 4 more Smart Citations
“…Previous research has suggested that decisionmakers refine their value estimates for choice options during deliberation, prior to committing to the choice (Lee & Daunizeau, 2020, 2021. It has been shown that the predictive effect of dV on consistency is larger when dV is calculated using postchoice ratings (i.e., dV2) rather than prechoice ratings (Lee & Coricelli, 2020;Lee & Daunizeau, 2020, 2021Lee & Hare, 2023;Lee & Holyoak, 2021; similar results were also reported in Simon, Krawczyk, et al, 2004;Simon & Spiller, 2016). The present study replicates this finding.…”
Section: Choice-induced Changes In Preference Are Instrumental To Dec...supporting
confidence: 88%
“…We then assessed the relationship between choice difficulty and SoA by regressing SoA on |dV1|. As in previous studies (Lee & Coricelli, 2020; Lee & Daunizeau, 2020, 2021; Lee & Hare, 2023; Lee & Holyoak, 2021), |dV1| had a reliable negative relationship with SoA in every experimental condition (Table 2).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations